Introduction to Epidemiology and Control of Peste des Petits Ruminants (Eco-PPR) tools. 2.2 Key informant interview (baseline)―Research guide - Wieland, Barbara; Dione, Michel M.; Okoth, Edward A.; Jones, B.; Kotchofa, Pacem; Ilboudo, Guy S.; Campbell, Zoë A.; Rutto, Erick (International Livestock Research Institute, 2020)
The goal of the key informant interviews is to get a general understanding of the study site before beginning other research activities.